2015
DOI: 10.1080/09593330.2014.997298
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment and activity of methanotrophic microorganisms from municipal wastewater sludge

Abstract: In this study, methanotrophic microorganisms were enriched from a municipal wastewater sludge taken from an Upflow Anaerobic Sludge Blanket reactor. The enrichment was performed in a sequencing batch reactor (SBR) with an autotrophic medium containing nitrite and nitrate. The microbial community composition of the inoculum and of the enrichment culture after 100 days of SBR operation was investigated and compared with the help of data obtained from 454 pyrosequencing analyses. The nitrite and nitrate removal e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 47 publications
0
5
0
1
Order By: Relevance
“…Metagenome analysis revealed that only a few phyla other than ‘ Candidatus Methanoperedens nitroreducens’ and NC10 phylum bacteria were represented in greater than 5% abundance. Anaerolineales (8.5% abundance) belonging to Chloroflexi are obligate anaerobes that have previously been observed in anaerobic methanotrophic (Ettwig et al 2009a ; Siniscalchi et al 2015 ) and methanogenic enrichment cultures (Gray et al 2011 ; Liang et al 2015 ; Yamada et al 2005 ). Anaerolineales may be responsible for the degradation of n -alkanes and release formate, acetate, hydrogen, and carbon dioxide.…”
Section: Discussionmentioning
confidence: 97%
“…Metagenome analysis revealed that only a few phyla other than ‘ Candidatus Methanoperedens nitroreducens’ and NC10 phylum bacteria were represented in greater than 5% abundance. Anaerolineales (8.5% abundance) belonging to Chloroflexi are obligate anaerobes that have previously been observed in anaerobic methanotrophic (Ettwig et al 2009a ; Siniscalchi et al 2015 ) and methanogenic enrichment cultures (Gray et al 2011 ; Liang et al 2015 ; Yamada et al 2005 ). Anaerolineales may be responsible for the degradation of n -alkanes and release formate, acetate, hydrogen, and carbon dioxide.…”
Section: Discussionmentioning
confidence: 97%
“…454 pyrosequencing is one of the popular high throughput sequencing analytical approaches which can sequence a certain number of DNA samples at the same time in one run (Ye and Zhang, 2013). The application of 454 pyrosequencing to evaluate microbial richness and 5 structure have been found in studies of SBR, membrane bioreactor (MBR), and many other biological wastewater treatment systems (Ng et al, 2015;Siniscalchi et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Further significant numbers of Chloroflexi were present. They are obligate anaerobes that have previously been found in both anaerobic methanotrophic (Ettwig et al 2009 ; Siniscalchi et al 2015 ) and methanogenic enrichment cultures (Yamada et al 2005 ; Gray et al 2011; Liang et al 2015). These Chloroflexi may degrade organic acids to formate, acetate, and hydrogen and feed the other community members (Hug et al 2013 ).…”
Section: Discussionmentioning
confidence: 99%